Visualization of Prestige in Hedonism Lifestyle in the Dance Work "ZoM" with Dramatic Dance Type - Rinaning Dina Karamani; Yanuartuti, Setyo (Solah, 2025)
ZoM's dance work is a dramatic dance work that reflects the consumptive lifestyle (hedonism) of Gen Z due to the influence of prestige in meeting the needs of social status. Gen Z born between 2001-2012 is known as a digitally native generation who is critical, independent, and innovative, but also close to a consumptive lifestyle. The focus of the content in this work refers to the theory of prestige by Sumarsono (2002) and the hedonistic behavior of Gen Z, while the focus of form uses dramatic theory by Smith, which highlights the dramatic atmosphere in the context of shopping activities in the Mall. The creation of the work uses the construction method I by Jacqueline Smith through the process of visual stimulation, ideation, exploration, improvisation, and refinement. This work consists of 7 scenes with 25 various movements, 30 floor patterns, and properties in the form of double triangles, box frames, and standing mirrors. Makeup and clothing are chosen according to the current style of Gen Z with bold and contrasting colors, as well as Music Instrument Digital Interface (MIDI) as accompaniment. ZoM is symbolically presented within the scope of a shopping mall and offers aesthetic ideas and social criticism of the phenomenon of prestige that triggers consumptive behavior in Gen Z, through visual, dramatic, and contemporary approaches.